Effects of Mango (Mangifera indica L.) and Guava (Psidium guajava L.) Extract on Frozen Chicken Meat Balls’ Storage Quality - Norhidayah, A.; Babji, A.S.; Shazali, M.S.; Norazmir, M.N.; Norazlanshah, H. (Pakistan Journal of Nutrition, 2011)
A study was carried out to determine the effect of mango and guava extract on frozen Chicken Meat Balls (CMB) storage quality. CMB were added with four different formulations; mango extract (400 ppm); guava extract (800 ppm); synthetic antioxidant (BHA) (200 ppm) and a control group. Antioxidant activities, Total Phenolic Compound (TPC), Ferum (III) Reducing Power (FRAP) and Ferric Thiocyanate (FTC) were also analyzed. Determination of Thiobarbituric Acid (TBA) test and Peroxide Value (PV) were done on CBM samples which had been stored in -18oC for 0, 1, 2 and 3 months and sensory evaluation for 0 and 2 months. TPC showed that mango had higher value at 548.77 μg/100 g fresh weight compared to guava at 222.09 μg/100 g fresh weight. FRAP value significantly (p